MYRTUS SPECIES PREVENTS REPRODUCTIVE TOXICITY INDUCED BY DOXORUBICIN IN MALE MICE - Abidli, Nacira; Ghaly, Inas S; Hassanane, Mahrousa M; Ekram S ahmed; Khalil, Wagdy K B (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Background: Myrtus sp is one of the natural products being used in Unani System of Medicine. Its leaves are frequently used for various ailments like diarrhoea, dysentery, vomiting and osmetic purposes. Objective: the main goal of the present work was to investigate protective effect of Myrtus sp extract against doxorubicin induced sperm abnormalities, genetic toxicity and gene expression alterations. Method: Plant samples were used to obtain plant extraction. Eighty male albino mice were allocated in several groups and treated with doxorubicin alone, doxorubicin plus Myrtus sp extracts for 30 days starting from 24 or 48h after doxorubicin treatment, or supplemented with Myrtus sp extracts for 30 days then treated with doxorubicin treatment. Results: The results revealed that treatment of male mice with doxorubicin then Myrtus sp for one month was the best treatment strategy for protection against doxorubicin induced toxicity. Whereas, Myrtus sp extract significantly preserved male mice from sperm abnormalities induced by doxorubicin treatment, genetic toxicity and gene expression alterations. Conclusion: The results suggested that phenolic compounds exist in the Myrtus sp extract might be contributed to prevention of the reproductive disorders and genotoxicity. Keywords: Myrtus sp, Doxorubicin, Sperm abnormalities, Genetic toxicity, Reproductive genes